Manajemen Anestesi pada Kehamilan Sistemik Lupus Eritematosus - Nuryawan, Iwan; Suryono, Bambang; Rahardjo, Sri (Jurnal Komplikasi Anestesi, 2018)
Systemic lupus erythematosus (SLE) is an autoimmune, multisystem disease, which involves complex pathogenetic mechanisms that can occur at all ages, characterized by the presence of direct autoantibodies against the core antigen. Management of lupus in women ideally begins before pregnancy occurs. Adequate analgesia can overcome the response of the organ system due to pain. Regional anesthesia techniques are very popular pharmacological techniques and become the gold standard because they provide optimal analgesia during labor with minimal side effects on the mother and fetus when compared with systemic or inhalation analgesia.